ANALISIS KUALITATIF DAN KUANTITATIF SENYAWA BIOAKTIF EKSTRAK KERANG MATA LEMBU (Turbo setosus) - El Viera, Baiq Vera; Sari, Dea Permata; Widiyawati, Ida Erna; Saepudin, Syumillah (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2025)
The rough turban snail (Turbo setosus) is a marine mollusk species often utilized as a traditional food source due to its high protein content and its empirically believed aphrodisiac properties. However, limited information is available on its bioactive compound content, so this study aims to be a preliminary study to analyze the bioactive compound content of the rough turban snail extract using qualitative and quantitative tests. Qualitative tests of bioactive compounds were carried out by adding various reagents that produce color changes or precipitate formation, while quantitative tests were carried out using UV-Vis spectrophotometry. The results of qualitative tests showed that the ethanol extract of the rough turban snail contains alkaloids, flavonoids, phenolics, steroids, and tannins. Quantitative tests gave results for phenolic content, flavonoid content, alkaloid content, and tannin content of 34.749 mg GAE/g extract, 11.6226 mg QE/g extract, 3.365 mg CE/g extract, and 332.79 mg TAE/g extract, respectively. The results of this study provide information on the bioactive compound content of T. setosus, which can be further developed as a natural product with pharmacological properties.